2002
DOI: 10.1097/00001665-200203000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Oral-Facial-Digital Syndrome Type II (Mohr Syndrome): Clinical and Genetic Manifestations

Abstract: The oral-facial-digital syndromes (OFDS) represent a heterogenous group of disorders characterized by oral malformation, facial anomalies, and digital anomalies. Type II OFDS was reported by Mohr in 1941. Mohr syndrome is an autosomal recessive inherited disease characterized by median cleft lip, poly lobed tongue, absence of medial incisors, and polydactyly of hands and feet. Some other different expressive types of OFDS cases have been reported, and identified with 11 different clinical entities up to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Median tongue clefts are reported in the literature to be associated with median lip clefts or median mandibular clefts 5,6,8,[10][11][12]14,16,17,19 . Median tongue or lip clefts are described also as being associated with orofacial digital syndromes Type I 8,16,17 , Type II (Mohr syndrome) 8,10,12,14 , Type IV (Mohr-Majewski syndrome) 5,11,14 and Type VI (Varadi syndrome) 14,19 .…”
mentioning
confidence: 99%
“…Median tongue clefts are reported in the literature to be associated with median lip clefts or median mandibular clefts 5,6,8,[10][11][12]14,16,17,19 . Median tongue or lip clefts are described also as being associated with orofacial digital syndromes Type I 8,16,17 , Type II (Mohr syndrome) 8,10,12,14 , Type IV (Mohr-Majewski syndrome) 5,11,14 and Type VI (Varadi syndrome) 14,19 .…”
mentioning
confidence: 99%
“…However, our patient had sib death with absent lower jaw and congenital heart. Because of the variable clinical expression, even intrafamilial, the attribution of the correct diagnosis among the several forms of OFDS is often difficult [35]. Considering the broad spectrum of anomalies of various organs, it has been proposed that OFD syndromes belong to the group of ciliopathies [4].…”
Section: Discussionmentioning
confidence: 99%
“…Review of the English literature back to 1950 revealed 58 reported cases of tongue hamartomas, including the largest review of 18 cases [4][5][6][7][8][9]. Four of the patients had In 12 cases, detailed information regarding age, gender, specific location on the tongue, and microscopic description of the hamartomas was lacking [6].…”
Section: Diagnosis and Discussionmentioning
confidence: 99%
“…Most cases of tongue hamartomas are not associated with any systemic condition, but 18 cases in the literature were documented to occur in association with Oral-Facial Digital Syndrome (OFDS) [4,[6][7][8]10], and one in association with Ectrodactyly-Ectodermal Dysplasia-Cleft Lip and Palate Syndrome (EECS) [9]. No cases of tongue hamartomas in Apert syndrome were documented.…”
Section: Diagnosis and Discussionmentioning
confidence: 99%